The prevalence and assessment of chronic kidney disease with diabetes: single center study - Gupta, B. B.; Vaidya, S. A.; Bhandari, Mahak; Behl, Simran; Kosta, Susmit (International Journal of Advances in Medicine, 2019)
Background: The prevalence of chronic kidney disease (CKD) and Type 2 diabetes (T2D) is increasing worldwide, information on Indian populations regarding the CKD patients with T2D is lacking. In this study, we examined the association of gender and age on the prevalence of other complications in CKD with T2D patients. Methods: A cross-sectional study was conducted at Sri Aurobindo Medical College, from March 2018 to April 2019. Source populations were all patients who came our medicine department for routine check-up. Results: A total of 163 CKD patients were included in the study. All the patients were randomly divided in two groups 61(37.4%) patients in CKD with T2D case group and 102 (62.5%) patients in CKD control group. Out of this 107 were males (65.6%) and 56 were females (34.3%). Male-to-female ratio and mean age were higher in the CKD with T2D group. The clinicopathological characteristics of CKD patients with T2D are even more complicated and severe disease in many ways. Conclusions: A male presents was higher as compare to female in CKD with T2D and control group. In present study there is significant difference in older and younger age in CKD with T2D and control group. Age, HNT, CVD, smoking, BMI, and 24-h urinary protein level were identified as possible contributors’ factors of CKD patients with T2D.